Interactive E-book in Problem-Based History Learning to Enhance Students' Knowledge of the Fall of the Dutch East Indies - Haidar Trisna Tanaya (Universitas Negeri Semarang, 2024)
History is often perceived as monotonous and unengaging by students, primarily due to traditional teaching methods focused on memorization with minimal interaction. This issue is exacerbated by the lack of innovative learning media aligned with technological advancements. This study aims to develop an interactive e-book as a history learning tool, integrating real-world problems, specifically